The Role of Work Ethic in Human Life - Mohammad Ghozali; Hamid Fahmy Zarkasyi; Kurnia Firmanda Jayanti; Yunita Wulandari (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study is to examine the role of work ethic in human life. Work ethic is a fundamental thing that can determine a person's behavior in meeting their needs. This study found an analysis of the relationship between work ethic, economic values and value systems in Islam. The method of this study is a qualitative method that combines observation, interviews, and documentation related to work ethic. This study is suggested and expected to researchers in developing research on work ethics, especially in relation to economic values.